The Impact of Human Resources Development and Organizational Culture on Employee Performance - E. Kosmajadi (Budapest International Research and Critics University, 2021)
Research is motivated by the phenomenon of low employee performance, presumably due to suboptimal human resource development and a less conducive organizational culture. The study aims to identify and analyze: a. human resource development, organizational culture, employee performance; b) the magnitude of the influence of human resource development on employee performance; c) the importance of the impact of organizational culture on employee performance; and the extent of the effect of human resource development and organizational culture on employee performance. This research uses a quantitative approach with a survey method. The data collection tool used a questionnaire distributed to 44 employees. The data obtained were analyzed descriptively and through a statistical process. The results showed: a. From the results of descriptive analysis of human resource development, organizational culture and employee performance are in good condition, but there are weaknesses in certain aspects. The results of the verification analysis show; b) human resource development has a significant effect on employee performance with a magnitude of influence of 66.69%; c) organizational culture has a significant impact on employee performance with the importance of the result of 51.84%; and d) the development of human resources and organizational culture together have an effect on employee performance with the magnitude of the influence of 78.30%, the remaining 21.70% is influenced by other factors that are not included in the model. In conclusion, both partially and simultaneously, human resources and organizational culture's development affects employee performance.